Policies to promote cereal intensification in Ethiopia: A review of evidence and experience - Byerlee, Derek; Spielman, David J.; Alemu, Dawit; Gautam, Madhur (International Food Policy Research Institute, 2007)
Despite more than a decade of policies placing high priority on cereal intensification, backed by one of the highest rates of public expenditures on agricultural in Africa, Ethiopia has yet to see payoffs in terms of higher and more stable cereal yields, reduced dependency on food aid, improved food security, and lower consumer prices for staples. There is understandable concern about the performance, efficiency and sustainability of the agricultural sector, specifically in terms of the current systems for providing extension services, improved seed, fertilizer, and credit. This paper aims to illuminate possible solutions available to improving the prospects for cereal intensification in Ethiopia. The paper traces the largely state-led policies that have been put in place to stimulate increased cereal productivity and examines the extent to which these policies have had their intended impacts. This review indicates that although Ethiopia has an admirable and sustained record of supporting seed-fertilizer technological intensification in cereals, the related state-led policies have outlived their usefulness, suggesting the need for a rethinking of approaches.